O efeito tipo panicolítico do tramadol em ratos submetidos ao teste do labirinto em T elevado - Fiaes, Gislaine Cardoso de Souza (2017)
Tramadol is a synthetic opioid widely prescribed for the treatment of moderate to severe pain, acting as an agonist on μ-opioid receptors and inhibiting serotonin (5-HT) and noradrenaline (NE) reuptake. Its monoaminergic mechanism is similar to tricyclic antidepressants, used in the treatment of panic disorder (PD) and in the treatment of pain. This study evaluated the effects of tramadol in rats submitted to the elevated T-maze (ETM), an animal model that evaluates behavioral parameters such as anxiety and panic. Male Wistar rats were treated acutely with tramadol (0.16 and 32 mg/kg) intraperitoneally (i.p.) and 30 minutes later they were submitted to the ETM. Tramadol (32 mg/kg) promoted a panicolytic-like effect. Considering that dorsal periaqueductal gray (dPAG) is the main brain structure related to the pathophysiology of PD, this study also evaluated the participation of serotonergic and opioid receptors located in the dPAG in the panicolytic-like effect of tramadol. Seven days after stereotactic surgery for implantation of a cannula in the dPAG, the animals were submitted to the test. To assess the involvement of 5-HT1A receptors on the effect of tramadol, we combined the 5-HT1A receptor antagonist, WAY100635 (0.37nmol/0.2μL/120s), microinjected intra-dPAG, 10 minutes prior to the administration of tramadol (32 mg / kg, ip). WAY100635 did not block the panicolytic-like effect of tramadol and promoted an anxiogenic-like effect when associated with tramadol. We also associated the non-selective opioid receptor antagonist, naloxone, administered systemically (1 mg/kg, ip) or intra-dPAG (0.5 nmol/0.5 μL/180s) 10 minutes prior to tramadol (32 mg/kg, ip). Both routes of administration showed that naloxone blocked the panicolytic-like effect of tramadol, showing that tramadol modulates panicolytic-like defensive behaviors through its interaction with opioid receptors located in dPAG.